Aging Impairs Disengagement From Negative Words in a Dot Probe Task - Talbot, Christine E.; Ksander, John C.; Gutchess, Angela (Frontiers in Psychology, 2018)
Age differences in emotional processes have been of great interest. Previous studies using the dot probe task show that older adults can be more influenced by negative emotionally-valenced faces than younger adults. Subsequent work has demonstrated two distinctive ways people engage with stimuli in this task, namely orienting to and disengaging from emotional stimuli. In the present study, we examined the effects of aging as well as ability to orient to and disengage from emotional words in a dot probe task. Older and younger adults viewed word pairs (positive-neutral, negative-neutral, and neutral-neutral) on a computer screen and pressed a button to identify a probe that replaced one of the words in the pair, responding as quickly as possible. Probes replaced either the emotional or neutral word. This design tests whether effects of aging were larger for disengaging (identifying a probe that replaced a neutral word in an emotional-neutral trial), compared to orienting (identifying a probe that replaced an emotional word in an emotional-neutral trial), and whether the pattern was exaggerated for negative compared to positive stimuli. Attentional bias estimates were calculated with mean reaction times for each trial-type. Older adults showed a specific impairment in disengaging from negative words. These results could reflect challenges with cognitive control and inhibition with age, which in this study are larger for older adults in the presence of negative information.